Structure and rheology of foams stabilized by different soybean varieties deficient in β-conglycinin subunits trimers. (October 2022) - Li, Jiaxin; Yang, Xiaoqing; Swallah, Mohammed Sharif; Amin, Khalid; Fu, Hongling; Ji, Lei; Meng, Xiangze; Song, Bo; Yu, Hansong; Jing, Wendan; Liu, Shanshan
Abstract: The need to replace animal protein with plant-based protein for foam formation is growing rapidly based on a variety of factors including sustainable environmental development, biosecurity, and limited option for vegetarians, which decreases the overall status of foam. The structure and rheology of foams made from soy protein isolate (SPI) deficient in β-conglycinin subunits (α′-lack SPI, α-lack SPI, and (α+α′)-lack) were explored in this study. Comparison of microstructure and the foaming characteristics of α′-lack SPI with those of Wild, α-lack SPI, and (α+α′)-lack SPI. Similarly, the microstructure demonstrated that different compositions of β-conglycinin subunits have potential influence on the secondary structure and density of SPI. The α′-lack SPI structure was closest and orderly arranged. The microstructure and foaming properties of α′-lack SPI were better than other SPI, which indicated that the α subunit in α′-lack SPI could generate fine bubbles with high stability. The interfacial shear rheological index of α′-lack SPI was also highest, so subunits may be related to the firmness of the air-water interface, foam rheology was shown to correlate not only to interfacial tension but also to the protein solutions' interfacial elasticity. (α+α′)-lack SPI has the lowest subunit content, foaming ability, and foam stability. This work was helpful to understand the air-liquid behavior of different subunit deficient SPI in β-conglycinin. It lays the foundation for the production of "plant active agents" with superior foaming properties based on soy protein. Graphical abstract: Image 1 Highlights: The difference in foaming properties of soy protein is endowed by three subunits, α, α′ and β. Fine bubbles prepared from α′-lack protein had the densest structure. α′-lack SPI exerts an outstanding foaming properties for different applications in food products. This study enlighten us on the association between air-liquid behavior of different subunit deficient SPI in β-conglycinin.